2010
DOI: 10.1120/jacmp.v12i1.3373
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and reproducibility of the VMAT plan delivery using three independent validation methods

Abstract: The complexity of VMAT delivery requires new methods and potentially new tools for the commissioning of these systems. It appears that great consideration is needed for quality assurance (QA) of these treatments since there are limited devices that are dedicated to the QA of rotational delivery. In this present study, we have evaluated the consistency and reproducibility of one prostate and one lung VMAT plans for 31 consecutive days using three different approaches: 1) MLC DynaLog files, 2) in vivo measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…Therefore, pre-treatment quality assurance (QA) for each patient is routinely performed in the clinic for verification that the plan is delivered as intended.3,5-9 Another method of verification to determine whether a VMAT plan is deliverable as intended or not is the analysis of dynamic log files registered in the linac control system during delivery. [10][11][12][13][14] As a further method of anal ysis, it has been suggested that the dose distribution in patient CT images be reconstructed with those dynamic log files and compared with that of the original treatment plan. 15 On the other hand, several studies have suggested modu lation indices for VMAT, which can quantify and evaluate the degree of modulation at the planning stage to verify the plan delivery accuracy.…”
mentioning
confidence: 99%
“…Therefore, pre-treatment quality assurance (QA) for each patient is routinely performed in the clinic for verification that the plan is delivered as intended.3,5-9 Another method of verification to determine whether a VMAT plan is deliverable as intended or not is the analysis of dynamic log files registered in the linac control system during delivery. [10][11][12][13][14] As a further method of anal ysis, it has been suggested that the dose distribution in patient CT images be reconstructed with those dynamic log files and compared with that of the original treatment plan. 15 On the other hand, several studies have suggested modu lation indices for VMAT, which can quantify and evaluate the degree of modulation at the planning stage to verify the plan delivery accuracy.…”
mentioning
confidence: 99%
“…[9][10][11] In addition, log file analysis can be used to assess the actual/relative delivered dose reconstructed on the patient anatomy using the patient's original CT image set 10,12 or the on-treatment cone-beam CT image set. 13 The use of log files within a radiotherapy VMAT dosimetry audit has been reported for Elekta linear accelerators 14 (Elekta AB, Stockholm, Sweden) but not for Varian linear accelerators.…”
Section: Introductionmentioning
confidence: 99%
“…However, the system has some issues that must be addressed, like electronic disequilibrium produced by insufficient build up material in EPID, inaccuracies in dose measurements created by scattered photons from the phosphor screen, and back scattered radiation from the support arms. Because the position of EPID is fixed with respect to the gantry, it is impossible to asses any errors in the gantry rotation [8]. Furthermore, EPID exhibits a small sag in its position due to gravity; this displacement also contributes to the reduction of pass rates, especially in VMAT plans in which gantry continuously rotates.…”
Section: Discussionmentioning
confidence: 99%
“…The diode-detector-based MapCHECK (Sun Nuclear Corporation, US) [7], the ion-chamber based Seven29 2D array (PTW, Germany) [8,9], and MatriXX (IBA Dosimetry, Germany) [10][11][12][13][14] are commonly used commercial 2D detector arrays. The MatriXX array has a linear response with dose and it is independent of energy [12].…”
Section: Introductionmentioning
confidence: 99%